Vitamin E Supplementation and Markers of Oxidative Stress in Indian Acute Myocardial Infarction Patients - Bhattacharya, Ijen; Saxena, Rahul; Saxena, Raj; Lal, Alok Milton (Asian Journal of Medical Sciences, 2013)
Background: Reactive oxygen species have been identified as mediators of cell injury in a variety of cardiovascular complications including Myocardial Infarction (MI). It is conceivable that vitamin E supplementation can be used therapeutically due to its role in ameliorating antioxidant status and free radicals scavenging activity. Aim: Therefore, the present study was undertaken to assess the markers of oxidative stress i.e. erythrocyte glutathione peroxidase (GSHPx) & malondialdehyde (MDA); plasma vitamin C, E, A and uric acid level in the blood samples of MI patients and to investigate the effect of in-vitro vitamin E supplementation in ameliorating the levels of these antioxidants in the blood sample of MI patients. Material & Method: 60 MI subjects (age group 30-60 years) were taken for the study and 60 healthy individuals served as controls. In-vitro vitamin E supplementation in the blood samples of MI subjects were performed and above mentioned parameters were estimated by using standard methods. Data was compared statistically by using student t-test. Result: Vitamin E supplementation brought about an improved antioxidants status with significantly raised vitamin C, E, A and GSHPx levels (p<0.05, p<0.001), and simultaneously depleted level of erythrocyte MDA (p<0.001) in blood samples of MI subjects. However, plasma uric acid levels remain unaltered (p<0.1). Conclusion: These findings further support the preventive and cardio protective role of vitamin E supplementation in reducing oxidative stress levels in the blood samples of MI patients. DOI: http://dx.doi.org/10.3126/ajms.v5i2.8430 Asian Journal of Medical Science, Volume-5(2) 2014: 46-53